The Influence of Islamic Human Development Index (I-HDI), Employment and Economic Growth on The Poverty Rate in The Province of North Sumatra - Ali, Osman; Nasution, Yenni Samri Juliati (Dinasti International Journal of Economics, Finance & Accounting, 2024)
North Sumatra is the 4th province with the most poor people in Indonesia. There are a total of 1.2 million poor people in 2023. This study aims to analyze the effect of Islamic Human Development Index (I-HDI), employment and economic growth on poverty in 33 districts / cities of North Sumatra in 2018-2023. The method used is panel data regression with random effect model estimation. The regression results show that the Islamic Human Development Index (I-HDI) has a negative and significant effect on the poverty rate in North Sumatra in 2018-2023. Labor absorption has a positive and significant effect on the poverty rate in North Sumatra in 2018-2023. While economic growth has a negative influence, but not significant. Simultaneously, the Islamic Human Development Index (I-HDI), labor absorption and economic growth have an influence on the poverty rate in North Sumatra in 2018-2023. One of the policy implications that can be done by the North Sumatra government to minimize the poverty rate is to improve the quality of human welfare and development not only seen from indicators of material achievement but also but also the achievement of non-material welfare, namely the existence of moral and spiritual values. In addition, the potential of unique resources must be improved and developed. This potential must be balanced with the quality and productivity of a good workforce in order to increase employment so that the people of North Sumatra can increase their income and get out of the poverty cycle.